Analiza razlik v samopodobi plesalk in plesalcev sportnega plesa ter primerjava z drugimi sportniki in sesportniki obeh spolov - Zaletel, P.; Tusak, M.; Tusak, M.; Zagorc, M. (Kinesiologia Slovenica, 2005)
The psychological dimension of self-concept is one of the most important for achieving top sports results. The goal of the research was to analyse and compare the selfconcept of female and male sport dancers in relation to other top-level athletes (track-and-field, skiing) and other non-athletes of both genders. The research included 283 individuals, with the data being analysed with one-way and two-way ANOVA. The self-concept comparisons were grounded on gender and inclusion in individual groups: athletes - dancers, other athletes and non-athletes of both genders. A significant difference was found in social ego in both female and male sport dancers, while most differences were identified between the groups of all athletes and non-athletes (social ego, identity, family ego, physical ego, personality ego, self-criticism). Both sport dancers and other top-level athletes of both genders have a higher general level of their self-concept and self-esteem compared with nonathletes of both genders.